2019
DOI: 10.1177/0886260519860083
|View full text |Cite
|
Sign up to set email alerts
|

Client-Initiated Violence Against Zambian Female Sex Workers: Prevalence and Associations With Behavior, Environment, and Sexual History

Abstract: Violence against women is a known risk factor for HIV and affects female sex workers (FSW) in sub-Saharan Africa. Little is known about the magnitude and determinants of violence against FSW in Zambia, where HIV and gender-based violence prevalence are high. We conducted a cross-sectional study, using multivariable logistic regression, to determine the prevalence and correlates of client-initiated physical violence among 419 FSW in Lusaka and Ndola. The prevalence of client-initiated physical violence was 39%.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 28 publications
(29 reference statements)
0
8
0
2
Order By: Relevance
“…Childhood maltreatment was a strong predictor of IPV perpetration in adulthood among men in Burundi 129. Across many countries, forced sexual debut was a risk factor for IPV in later life among female sex workers,88 126 130 131 and among adolescent girls and young women 111 116 132…”
Section: Resultsmentioning
confidence: 99%
“…Childhood maltreatment was a strong predictor of IPV perpetration in adulthood among men in Burundi 129. Across many countries, forced sexual debut was a risk factor for IPV in later life among female sex workers,88 126 130 131 and among adolescent girls and young women 111 116 132…”
Section: Resultsmentioning
confidence: 99%
“…An established prospective cohort of HIV-uninfected high-risk women (HRW) in Lusaka and Ndola, Zambia was examined. 1113 The women included were either FSWs or single mothers with children under the age of five (SM) referred to the Zambia-Emory HIV Research Project (ZEHRP) from local post-natal clinics or invited from community outreach at sex work hot spots.…”
Section: Methodsmentioning
confidence: 99%
“…Informal security arrangements within lodges or bars offer some form of protection. Research in Zambia (Malama et al, 2019) confirms that recruiting clients from the streets is a risk factor for violence. Sex taking place in open spaces rather than houses or hotels (Schwitters et al, 2015), and sex occurring in clients’ homes (Malama et al, 2019) were found to be associated with violence.…”
Section: Resultsmentioning
confidence: 94%
“…Research in Zambia (Malama et al, 2019) confirms that recruiting clients from the streets is a risk factor for violence. Sex taking place in open spaces rather than houses or hotels (Schwitters et al, 2015), and sex occurring in clients’ homes (Malama et al, 2019) were found to be associated with violence. Malama et al(2019) report that the odds of client-initiated physical violence were higher for Zambian WSS who lived in the capital of Lusaka than those living in the second largest city, Ndola.…”
Section: Resultsmentioning
confidence: 94%